Neural Markers of Knee Disability in Patients with Anterior Cruciate Ligament Reconstruction: A Multicenter fMRI Study (108). Issue 10 (31st October 2021) - Criss, Cody; Lepley, Adam; Simon, Janet; Onate, James; Clark, Brian; Grooms, Dustin
Objectives: Anterior cruciate ligament (ACL) rupture is a common knee injury among athletes and physically active adults. Despite surgical reconstruction and extensive rehabilitation, reinjury rates remain high and patient-reported disability continues even years after therapy and return to activity. Prolonged knee dysfunction has been attributed, in part, to unresolved neuromuscular deficits of the surrounding joint musculature in response to injury. Recent reports have identified widespread cortical and spinal cord changes to engage the quadriceps following injury, which may explain why a considerable proportion of patients exhibit persistent levels of knee disability. While these reports have provided evidence for consequences of injury that extend beyond the joint, there is a paucity of studies exploring the link between nervous system functioning and patient-reported measures of disability.The objective of this study was to determine the relationship between patient-reported knee disability and neural activity for knee control in patients with ACL reconstruction (ACL-R). Methods: In this multicenter cross-sectional study, twenty-five participants with unilateral ACL-R (18 left, 7 right; 10 males, 15 females; age, 21.8 ± 2.6 years; height, 169.7 ± 19.2 cm; weight, 69.6 ± 14.8 kg; Tegner activity level scale, 8.4 ± 1.2; IKDC, 84.9 ± 10.8; graft type, 15 quadrupled hamstring tendon / 10 bone-patellar-tendon-bone; time from surgery, 51.6 ± 32.0 months) underwent functional magnetic resonance imaging (fMRI) testing. fMRI testing consisted of repeated cycles of open-chain knee flexion/extension movement (Figure 1A). Neural activation patterns were quantified using blood-oxygen-level-dependent (BOLD) signals for all participants during the movement task at a cluster corrected z-threshold >2.3, p <.05 (Figure 1B). Regions of interest (ROI) were generated using the Juelich Histological Brain atlas Pearson product-moment correlations were used to determine the relationship mean BOLD signals within each ROI and levels self-reported knee disability, measured using the International Knee Documentation Committee (IKDC) index. False-discovery-rate correction using the Benjamini-Hochberg procedure was applied to adjust for multiple comparisons. Results: ACL-R self-reported IKDC scores were positively related with neural activity within the ipsilateral secondary somatosensory cortex, S2 ( r =0.57, p =.005), and premotor cortex, PMC ( r =0.48, p =.02), after controlling for sex and time from surgery (Table 1, Figure 2-3). Conclusions: These data suggest increases in secondary sensorimotor activity (premotor, secondary somatosensory cortices) report greater levels of perceived knee function in patients following ACL-R. The S2 largely functions as a center for processing varied levels of somatosensory information. The PMC, on the other hand, receives a considerable number of sensory inputs but operates to guide voluntary movements. Therefore, increased recruitment of these regions may improve functionality to the knee or provide a neurologic mechanism to compensate for joint instability or the loss of afferent fibers within the ACL, in turn reducing levels of self-reported knee disability. Future investigations should determine if ACL-R patients with low self-reported disability would benefit from rehabilitation approaches that target these brain regions across the therapeutic window.